The exploration of mystical experiences among religious preachers - Rida Irfan; Ayesha Aziz (Institut Agama Islam Negeri Langsa, 2021)
The current qualitative study aimed to explore the mystical experiences among religious preachers. A purposive sampling technique was employed to select a sample of (n=10) religious preachers who had encountered at least one mystical experience. The transcendental phenomenological approach was used to capture the essence of the mystical experiences through an in-depth semi-structured interview guide based on five domains: the exploration of mystic features, beliefs, impact on life, sharing of mystical experiences, and the religious and cultural oriented explanations. The modification of Stevick-Colaizzi-Keen’s model by Maustakas (1994) was employed for data analysis followed through a series of steps such as bracketing, horizonalization of data, a grouping of significant statements to constitute themes (triggers, perceptual experience, symbolism and derived meanings, significant figures, reaction, and the cultural explanation of mystical experiences), textural description and a structural description with verbatim examples was developed. These descriptions were combined to write a composite description that reflected the ‘essence’ of the mystical experiences and highlighted the causes, characteristics, perceptual experiences, beliefs, and impact. The findings highlighted the subjective nature of the mystical experiences and the need to develop an indigenous formal criterion to identify such experiences.